OASL enhances mRNA translation and reprograms lipid metabolism to promote cancer progression - Shi-Bing Li; Li Yuan; Qian-Ying Zhu; Gong Zhang; Yuan-Tao Liu; Ming-Hui Gao; Fei Han; Zhi-Rui Lin; Hua Zhang; Lin-Quan Tang; Li Sun; Qing-Yu He; et al. (Cell Reports, 2025)
Summary: Type I interferons (IFN-Is) are central coordinators of tumor-immune system interactions. Accumulating evidence suggests that persistent IFN-Is and a subset of IFN-stimulated genes (ISGs) might promote tumor development, but the regulation of mRNA translation and lipid metabolism during this process remains unknown. Here, we report that oligoadenylate synthetase-like (OASL) is a key ISG in mediating the pro-tumor effects of IFN-Is. OASL is highly expressed in human cancers and is associated with poor prognosis. We identify physical and functional interactions between OASL and ribosome. OASL enhances global translation initiation with the preference for a subset of mRNAs involved in fatty acid (FA) synthesis by interaction with ribosomes. Using both loss- and gain-of-function studies, we find that OASL reprograms FA metabolism to enhance oncogenesis, which can be inhibited by an FA synthesis inhibitor. Our results define OASL as an important factor in regulating mRNA translation, mediating tumor-promoting functions of IFN-Is, and providing potential therapeutic interventions.